ENHANCING THE POTENTIAL OF SMALL HYDROELECTRIC PLANTS: A COMPREHENSIVE REVIEW - Tojimurodov Dilshodbek Dilmurodjon o’g’li (TADQIQOTLAR.UZ, 2024)
Abstract: Small hydroelectric plants have emerged as a promising avenue for sustainable energy generation, offering numerous benefits including minimal environmental impact and localized power production. However, their capacity has often been limited by various factors. This article reviews recent advancements aimed at increasing the capacity of small hydroelectric plants, encompassing technological innovations, regulatory frameworks, and economic incentives. By addressing these challenges, we aim to unleash the full potential of small hydroelectric plants in meeting the growing demand for clean energy.